2002
DOI: 10.1021/la0157263
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Hydrogen Adsorption and Desorption on Silica-Supported Pt, Rh, and Ru Catalysts Studied by Solid State 1H NMR

Abstract: The kinetics of adsorption and desorption of hydrogen on the multifaceted surfaces of silica-supported Pt, Rh, and Ru catalysts were studied by means of solid state 1H NMR. Experiments with selective inversion of 1H magnetization and the formalism developed by Engelke et al. [J. Chem. Phys. 1994, 101 (9), 7262] were used to extract the adsorption and desorption rate constants and the apparent sticking coefficient. The sticking coefficients of hydrogen measured at 333 K at a surface coverage of 0.4 over 5% Pt/S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…As hydrogen pressures and coverages increase, H 2 chemisorption becomes less exothermic, reportedly decreasing to anywhere from -50 kJ mol -1 to -35 kJ mol -1 on Ru (0001) depending on the hydrogen coverage [67,84]. On supported catalysts, King has reported that the enthalpy of H 2 chemisorption on a 4% Ru/SiO 2 catalyst decreases to -43 kJ mol -1 at a fractional hydrogen coverage of 0.4 [85] and further to -20 to -30 kJ mol -1 as the surface approaches hydrogen saturation [86]. In addition, the presence of co-adsorbates will generally decrease hydrogen binding energies.…”
Section: Microkinetic Analysis: Regression Resultsmentioning
confidence: 99%
“…As hydrogen pressures and coverages increase, H 2 chemisorption becomes less exothermic, reportedly decreasing to anywhere from -50 kJ mol -1 to -35 kJ mol -1 on Ru (0001) depending on the hydrogen coverage [67,84]. On supported catalysts, King has reported that the enthalpy of H 2 chemisorption on a 4% Ru/SiO 2 catalyst decreases to -43 kJ mol -1 at a fractional hydrogen coverage of 0.4 [85] and further to -20 to -30 kJ mol -1 as the surface approaches hydrogen saturation [86]. In addition, the presence of co-adsorbates will generally decrease hydrogen binding energies.…”
Section: Microkinetic Analysis: Regression Resultsmentioning
confidence: 99%
“…Part of this differing behavior can be ascribed to near saturation (or zero) coverage of adsorbates present on the cluster surfaces (inset Figure a,b) under varying conditions, a dependency that is directly correlated with the gas partial pressure, temperature, and adsorbate bonding strength. Simple thermochemical kinetic calculations suggest, for example, that the coverage of H on Pt at 673 K is very low at the partial pressures we have examined . Minimal changes in the absolute integrated intensity with varying partial pressure are therefore expected in this regime.…”
Section: Discussionmentioning
confidence: 83%
“…Simple thermochemical kinetic calculations suggest, for example, that the coverage of H on Pt at 673 K is very low at the partial pressures we have examined. 76 Minimal changes in the absolute integrated intensity with varying partial pressure are therefore expected in this regime. In contrast, the stronger bonding of CO on Pt suggests that a significant coverage will still exist at 673 K (slightly above the desorption temperature) for higher partial pressures but not for the lower partial pressures.…”
Section: Discussionmentioning
confidence: 91%
“…There is precedence for such a mechanism. It is known that kinks, steps, and other forms of crystal roughness can, in conjunction with adsorbate mobility, affect the extent to which adsorption occurs , and facilitate adsorption to the remainder of the surface, as is the case for the portal model. , Several examples of adsorption which may meet the conditions for the two-well 2D gas model are H 2 O on TiO 2 , O 2 on Au, CO on Cu, , O 2 on graphite, , hydrogen adsorption on silica-supported transition metals, O 2 adsorption on transition metal surfaces with alkali metal adatoms, , and acetone adsorption on TiO 2 . The two-well 2D gas model may play a role in catalysis, where defects, steps, kinks, etc., are commonly the most active sites. ,, …”
Section: Discussion and Derivations Of Adsorption Modelsmentioning
confidence: 99%